2014
DOI: 10.1021/ja503117q
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ester Groups Switch Selectivity: Diastereodivergent Synthesis of Tetracyclic Spiroindolines

Abstract: Stereocontrol in the synthesis of structurally complex molecules, especially those with all-carbon quaternary stereocenters, remains a challenge. Here, we reported the preparation of a class of tetracyclic cyclopenta-fused spiroindoline skeletons through Cu(II)-catalyzed intramolecular [3 + 2] annulation reactions of donor-acceptor cyclopropanes with indoles. Both cis- and trans-diastereomers of tetracyclic spiroindolines are accessed with high selectivities by altering the remote ester groups of cyclopropanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…Isopropyl esters favored the trans diastereomer, whereas 2‐adamantyl esters were best for the cis diastereomer. Density functional theory calculations indicated that attractive forces, such as dispersion force, between the ester group and the indole favored generation of the trans isomer, whereas formation of the cis isomer was preferred when steric repulsion was large (Scheme ) …”
Section: [3+2] Cyclizationsmentioning
confidence: 99%
“…Isopropyl esters favored the trans diastereomer, whereas 2‐adamantyl esters were best for the cis diastereomer. Density functional theory calculations indicated that attractive forces, such as dispersion force, between the ester group and the indole favored generation of the trans isomer, whereas formation of the cis isomer was preferred when steric repulsion was large (Scheme ) …”
Section: [3+2] Cyclizationsmentioning
confidence: 99%
“…111115 In the previous studies, substituents at the C2- and/or C3-positions of indoles were required for appropriate regiocontrol. 111114 For example, the dirhodium(II)-catalyzed [3+2]-cycloaddition reaction between ( E )-styryldiazoacetate and N -methylindole 32a only afforded moderate regioselectivity (4:1 rr). 112 Recently, this limitation has been overcome by the employment of enoldiazoacetamides 31 in dearomatizing [3+2]-cycloaddition with C2,C3-unsubstituted indoles 32 , which provided cyclopentane-fused indoline derivatives 33 with exceptional regio-, diastereo-, and enantiocontrol (Scheme 13).…”
Section: Mecc Reactions Of Enoldiazo Compoundsmentioning
confidence: 99%
“…Stereoselective intramolecular [3+2] annulation reactions of DA cyclopropanes with indoles have also been investigated . With Cu(II)/ 24 as the catalyst, a class of tetracyclic cyclopenta‐fused spiroindoline skeletons were constructed through the aforementioned strategy.…”
Section: [3+n] Annulations Of Da Cyclopropanesmentioning
confidence: 99%
“…This method was applied to the synthesis of optically active tetracyclic spiroindolines. By employing the optically pure isopropyl or 2‐adamantyl substrate, the intramolecular [3+2] products were furnished with complete retention of the enantiomeric purity (Scheme ) …”
Section: [3+n] Annulations Of Da Cyclopropanesmentioning
confidence: 99%